Critical Thinking in the Algerian Secondary School EFL Class - Achoura, Meriem; MERROUCHE , Sarah (Journal of Human Sciences, 2021)
The present study investigates the teaching of critical thinking (CT) in the Algerian secondary school EFL class. The study included 76 EFL teachers from different schools in the Wilaya of Oum El Bouaghi. They were handed in a questionnaire that investigated whether they think that they teach CT or not. On the other hand, a classroom observation of eleven (11) teachers was conducted for the purpose of comparing their beliefs to their in-class practices. The results displayed a clear absence of the teaching of CT although the teachers believed that they teach it.